NI-3 FEASIBILITY OF MRI PERFUSION IN DISCRIMINATING BETWEEN EDEMA AND INFILTRATIVE AREAS IN THE PERI-GBM NON-CONTRAST T2 WEIGHTED HIGH AREA. (3rd December 2022) - Kuroda, Hideki; Okita, Yoshiko; Arisawa, Atsuko; Utugi, Rena; Tachi, Tetsuro; Hirayama, Ryuichi; Kijima, Noriyuki; Nakamura, Hajime; Kagawa, Naoki; Kishima, Haruhiko
Abstract: Background: Glioblastomas are highly infiltrative tumors, and differentiating between infiltrating tumors and vasogenic edema occurring in the non-enhancing T2-weighted hyperintense area is challenging. Here, we differentiated between infiltrating tumors and edemas in glioblastomas using dynamic perfusion-weighted MR imaging. Methods: Data were collected from 33 patients with glioblastomas and 15 with meningioma as controls, who underwent resection at our institution between January 2019 and March 2022. The MRI data included T2 weighted images and contrast-enhanced T1 weighted images, and dynamic perfusion-weighted MR imaging. Two neurosurgeons manually assigned regions of interest (ROIs) to infiltrating tumors and vasogenic edema based on a previous report using conventional MRI features. The ratio of cerebral blood volume (CBV), cerebral blood flow (CBF), and mean transit time (MTT) in the ROIs to that contralateral normal regions were calculated. We also histological analysis using histological specimens obtained by stereotactic biopsy in each ROI. Results: CBF and MTT ratios of infiltrating tumors and edemas differed significantly (p<0.01), while CBF and MTT ratios of edemas and controls showed similarities. MTT values of controls and infiltrating tumors differed significantly (p=0.02). Receiver operating characteristic curve analysis revealed that CBF (area under the curve [AUC]=0.81) and MTT(AUC=0.95) were effective in distinguishing between infiltrating tumors and edemas. Pathological analysis revealed that cell density, MIB1-index, and microvessel density were higher in infiltrating tumors than in edemas. Conclusions: Using dynamic perfusion-weighted MR imaging may prove useful in differentiating infiltrating tumors from edemas in the non-contrast T2 hyperintensity region of glioblastomas.